ASSESSMENT OF THE SUSTAINABILITY OF WATER AND SANITATION SYSTEMS IN RURAL VILLAGES THROUGH INDICATORS. AN EXPERIENCE OF CONCEPTUAL DESIGN AND APPLIED SOFTWARE IN PERU (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The main objective of the present research was to apply the sustainability approach to the management of sanitation systems carried out by community-based organizations (JASS) in rural villages with the support of the district municipality. Given the limited capacity of rural district municipalities to supervise, monitor and provide technical assistance to these community organizations, a proposal for municipal technical assistance (MTA) was developed based on an index for the evaluation of the sustainability of rural sanitation systems (IESSSR). Such index allowed to evaluate not only the sustainability, but also to identify the deficient and unsustainable aspects of each system, which was crucial to develop improvement plans for each JASS. A first measurement of the sustainability of the two intervened systems was made – of the rural population centres of Palmira and Dos de Mayo, both located in the district of Leymebamba –, a general sustainability index (IGS) for JASS Palmira of 3.010 (Stable) and for Dos de Mayo of 2.997 (Unstable) were obtained.  In the second measurement, using 5 dimensions, 18 factors, 48 variables and 66 indicators, the IGS of JASS Palmira was 3.179 (Stable) and that of Dos de Mayo was 3.233 (Stable). The reliability of the index was analysed using the test-retest method by comparing the May and December measurements of each JASS, obtaining a Pearson correlation index of 0.631 for Palmira and 0.602 for Dos de Mayo. Finally, the index was developed into a software application to facilitate the storage, processing, monitoring, evaluation and presentation of the information, and is currently being tested in the municipality of Leymebamba.